2019
DOI: 10.2147/tcrm.s200813
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gamma Knife Radiosurgery For Brain Vascular Malformations: Current Evidence And Future Tasks</p>

Abstract: Gamma Knife radiosurgery (GKRS) has long been used for treating brain vascular malformations, including arteriovenous malformations (AVMs), dural arteriovenous fistulas (DAVFs), and cavernous malformations (CMs). Herein, current evidence and controversies regarding the role of stereotactic radiosurgery for vascular malformations are described. 1) It has already been established that GKRS achieves 70–85% obliteration rates after a 3–5-year latency period for small to medium-sized AVMs. However, late radiation-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…However, larger AVMs require multiple procedures, with treatment intervals ranging from 3 to 6 months. The occlusion rate ranges from 33%-72% in treating larger AVMs[ 13 ]. We discontinued this treatment because of its lengthy duration and unpredictable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, larger AVMs require multiple procedures, with treatment intervals ranging from 3 to 6 months. The occlusion rate ranges from 33%-72% in treating larger AVMs[ 13 ]. We discontinued this treatment because of its lengthy duration and unpredictable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on size, Gamma Knife radiosurgery (GKRS) is ideal for small AVMs (< 3 cm). 12 Decisions on the management of cerebral AVMs are still being debated due to a lack of data on the risk of hemorrhage as well as predictors and treatment complications. 13 The main goal of treatment for brain AVM is complete nidus obliteration to prevent rebleeding and potential neurological deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…The main secondary effects reported following GammaKnife ® SRS for AVMs are: hemorrhage, radionecrosis and, in the long term, occurrence of cysts, chronic encapsulated hematoma and secondary cancers [51]. Among 581 patients treated with GammaKnife ® and followed during a median time of 10.1 years, Hasegawa et al reported cumulative incidence rates of cyst formation and encapsulated hematomas estimated at 2.8% at 10 years and 9.7% at 20 years, respectively [52].…”
Section: Gammaknife ® Stereotactic Radiosurgerymentioning
confidence: 99%